COPROX Fixed Bed Reactor – Temperature Control Schemes - Giunta, Pablo Daniel (2012)
In this paper, different temperature control schemes for the COPROX stage of a 5 kW fuel cell system were analysed. It was found that, among the schemes proposed, i.e. co- and counter- current heat exchange, single adiabatic reactor and series of adiabatic reactors with interstage heat exchange, the best choice for temperature control was the series of adiabatic reactors with interstage heat exchange. This scheme represented the best way to keep the average temperature around 443 K, which was found to be the most suitable temperature for selectivity towards the CO oxidation. If hydrogen is produced from ethanol steam reforming, the heat withdrawal can be carried out by the water/ethanol reformer feed mixture, thus contributing to the energy integration of the overall system.